Cord Direct Antiglobulin Test for Predicting the Need for Phototherapy in Neonates with ABO Incompatibility: A Prospective Cohort Study - Ranjith Balan; Sakthipriya Balaji; Arun Kumar; Subash Sundar; Shrinidhi Krishnan; Ashok Chandrasekaran (Journal of Clinical and Diagnostic Research)
Introduction: The Direct Antiglobulin Test (DAT) is a screening technique used to detect Immunoglobulin G (IgG) antierythrocyte antibodies on foetal Red Blood Cells (RBCs). Universal bilirubin screening decreases the incidence of severe hyperbilirubinemia. The diagnostic efficacy of DAT in cases of ABO incompatibility is not well established, in contrast to Rh incompatibility. Aim: To evaluate the diagnostic ability of routine cord blood DAT in neonates ≥35 weeks of gestation with ABO incompatibility in predicting the requirement for phototherapy. Additionally, to compare the diagnostic ability between two methods of DAT estimation, namely the semiagglutination gel method and the conventional tube method. Materials and Methods: This prospective cohort study was conducted from September 2022 to March 2024 at SRM Medical College Hospital and Research Centre, Chennai, Tamil Nadu, India. Following the acquisition of informed consent, cord blood samples were collected from 934 neonates delivered after 35 weeks of completed gestation to mothers with O blood type. In cases of ABO incompatibility (523 neonates), DAT was performed using both the manual tube method and the automated semiagglutination gel method in the blood bank. Serum bilirubin levels, complete blood counts with peripheral smear analysis and reticulocyte counts were performed on day 3 or earlier, as clinically indicated. The neonates were treated in accordance with the American Academy of Paediatrics (AAP) 2004 recommendations on phototherapy. Babies were monitored for jaundice until 14 days of age. Results: Out of 3,092 eligible deliveries, 523 babies with ABO incompatibility were enrolled. The baseline characteristics were comparable. Bilirubin levels in DAT-positive and DAT-negative neonates were 14.60±3.58 mg% and 13.18±3.16 mg% (p-value <0.001), respectively. The adjusted odds ratio of positive DAT for both methods in predicting the requirement for phototherapy was 3.21 (95% CI 2.1-5.8). The sensitivity, specificity, positive likelihood ratio and negative likelihood ratio of the tube method were 37.5%, 85.16%, 2.53, and 0.73, respectively, while for the gel method they were 37.08%, 86.57%, 2.76, and 0.73, respectively. Conclusion: In cases of ABO incompatibility, neonates with positive cord DAT had higher odds of requiring phototherapy; however, a high negative likelihood ratio indicates that additional factors may be involved in hyperbilirubinemia that necessitate phototherapy.